Factors mediating the psychological well-being of healthcare workers responding to global pandemics: A systematic review. (July 2022) - Schneider, Jekaterina; Talamonti, Deborah; Gibson, Benjamin; Forshaw, Mark
This paper reviewed mediators of psychological well-being among healthcare workers responding to pandemics. After registration on PROSPERO, a systematic review was performed in four databases and 39 studies were included. Worse mental health outcomes, such as stress, depressive symptoms, anxiety and burnout were related to demographic characteristics, contact with infected patients and poor perceived support. Self-efficacy, coping ability, altruism and organisational support were protective factors. Despite limitations in the quality of available evidence, this review highlights the prevalence of poor mental health in healthcare workers and proposes target mediators for future interventions.